Study of QPSK Modulator and Demodulator in Wireless Communication System Using MATLAB - Abdel-Razeq, Sharief Nasr; Al-Azzeh, Areej Salah; Ayyoub, Rawan Yousef (International Journal of Interactive Mobile Technologies (iJIM), 2013)
Quadrature Phase-Shift Keying (QPSK) modulation technique is one of the most widely used modulation scheme in modern digital communication system; it provides high performance on bandwidth efficiency. In this paper, the model of QPSK modulator and demodulator has been simulated using MATLAB Simulink.